Iron(II) Clathrochelate with Terminal Triple C≡C Bond and Its Carboranoclathrochelate Derivative with a Flexible Linker between the Polyhedral Cages: Synthesis and X‐Ray Structure. Issue 39 (22nd October 2019) - Zelinskii, Genrikh E.; Belov, Alexander S.; Vologzhanina, Anna V.; Limarev, Ilya P.; Pavlov, Alexander A.; Olshevskaya, Valentina A.; Makarenkov, Anton V.; Dorovatovskii, Pavel V.; Lebed, Ekaterina G.; Voloshin, Yan Z.
Abstract: Monopropargylamine iron(II) tris‐dioximate was easily prepared in a high yield using nucleophilic substitution of its monochloroclathrochelate precursor with propargylamine as a primary aliphatic amine N ‐nucleophile in acetonitrile as a solvent. This complex with terminal C≡C group underwent a 1, 3‐dipolar cycloaddition "click"‐reaction with ortho ‐carborane‐1‐methylazide, thus giving a hybrid iron(II) carboranoclathrochelate with ortho ‐carborane‐(12)‐[1, 2, 3]‐triazolmethylamine fragment in its ribbed substituent, the molecule of which contains two ( i. e . clathrochelate and carborane) terminal cages. These complexes were characterized using elemental analysis, MALDI‐TOF mass, IR, UV‐Vis, 1 H, 1 H 11 B, 11 B, 11 B 1 H, 19 F 1 H and 13 C 1 H NMR spectra, and by single crystal X‐ray diffraction as well. Abstract : Monopropargylamine iron(II) tris‐dioximate was easily prepared in a high yield using nucleophilic substitution of its monochloroclathrochelate precursor with propargylamine as a primary aliphatic amine N ‐nucleophile in acetonitrile as a solvent. This complex with terminal C≡C group underwent a 1, 3‐dipolar cycloaddition "click"‐reaction with ortho ‐carborane‐1‐methylazide, thus giving a hybrid iron(II) carboranoclathrochelate with ortho ‐carborane‐(12)‐[1, 2, 3]‐triazolmethylamine fragment in its ribbed substituent, the molecule of which contains two ( i. e . clathrochelate and carborane) terminal cages.